(untitled) (Ames, Iowa, 2006)
The biochemistry of food is the foundation on which the research and development advances in food biotechnology are built. In Food Biochemistry and Food Processing, lead editor Y.H. Hui has assembled over fifty acclaimed academicians and industry professionals to create this indispensable reference and text on food biochemistry and the ever-increasing development in the biotechnology of food processing. While biochemistry may be covered in a chapter or two in standard reference books on the chemistry, enzymes, or fermentation of food, and may be addressed in greater depth by commodity-specific texts (e.g., the biotechnology of meat, seafood, or cereal), books on the general coverage of food biochemistry are not so common. Food Biochemistry and Food Processing effectively fills this void.
Thực tập chuyên ngành ngoài trường,Hóa sinh thực phẩm
Keywords: Food industry and trade,Công nghệ chế biến và kinh doanh thực phẩm,Food technology,Công nghệ thực phẩm; Research,Nghiên cứu